Caffeine effect on extending time to exhaustion - Namešanský, J.; Hrnciriková, I.; Smolka, O. (Journal of Human Sport & Exercise, 2014)
The purpose of this study was to determine the effect of different doses of caffeine on extending time to exhaustion in long-term endurance exercise. Using a placebo-controlled, double-blind crossover study design, 10 hobby male cyclists (30.3 ± 5.8 y; BMI = 23.5 ± 1.6, VO2max = 56.9 ± 6.6 ml/kgxmin) completed three experimental tests. Each test consisted of 1-h steady-state cycling on static ergometer at 70% VO2max load immediately followed by graded exercise test to exhaustion (2.3 W/s). Either placebo or 0 or 7 mg/kg BM of synthetic caffeine with 0.5 l water and maximum of 0.5 mg/kg BM of carbohydrate gel were administered 70 minutes prior to the test. Total exercise time was significantly (p < 0.05) extended by the 7 mg/kg BM of caffeine compared with placebo. Significant (p < 0.05) extension of total exercise time was observed also by the 7 mg/kg compared with 2 mg x kg?¹. No statistically (p = 0.97) significant differences were observed between 2 mg/kg compared with placebo. Positive effect of caffeine on long-term endurance in hobby cyclist was observed only after ingestion of high dosage (7 mg/kg BM). Low dosage (2 mg/kg) didn`t show any ergogenic effect compared with placebo. This result might not be generalized, but rather shows ambiguous effects of this substance.